Adherence to face mask use during the COVID-19 pandemic among women seeking antenatal care in Kinshasa, Democratic Republic of Congo: a facility-based cross-sectional study. Issue 7 (8th July 2022) - Nkamba, Dalau Mukadi; Arena, Patrick J; Gadoth, Adva; Hoff, Nicole A; Dzogang, Camille; Kampilu, David; Beya, Michael; Wong, Hui-Lee; Anderson, Steven; Kaba, Didine; Rimoin, Anne W
Abstract : Objectives: To describe face mask use among pregnant women seeking antenatal care (ANC) in Kinshasa, Democratic Republic of Congo and to identify factors associated with masking adherence in this population. Design: Facility-based cross-sectional study nested within a prospective cohort study. Setting: Random sample of 10 health facilities, including 5 primary health centers and 5 secondary facilities or hospitals. Participants: A total of 934 pregnant women aged 18 years or above with a gestational age of at least 32 weeks were consecutively surveyed from 17 August 2020 to 31 January 2021. Primary and secondary outcome measures: We estimated the proportions of pregnant women wearing a face mask and masking correctly (ie, over the mouth and nose), and assessed their knowledge regarding the COVID-19 pandemic. Multivariable logistic regression was employed to identify factors associated with overall and correct face mask use. Results: Overall, 309 (33.1%) women wore a mask during the interview after their antenatal appointments, but only 33 (10.7%) wore a mask correctly. The odds of masking and correct mask use were significantly higher among women who had their ANC visit in a facility that provided COVID-19 care. Additionally, women who experienced COVID-19-like symptoms in the past 6 months had higher odds of wearing a mask correctly compared with those reporting no recent symptoms. Although 908 (97.2%) women were aware of the COVID-19 pandemic, only 611 (67.3%) thought that COVID-19 was circulating locally in Kinshasa. Conclusion: Overall and correct face mask adherence levels were low among pregnant women attending ANC in Kinshasa. Our study highlights the need for improving adherence to correct face mask use in order to help control the spread of COVID-19 within Kinshasa alongside other control measures, like vaccination.